2005
DOI: 10.1111/j.1601-0825.2005.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of periodontal bacteria and Porphyromonas gingivalis fimA variations with phenytoin‐induced gingival overgrowth

Abstract: Type II Pg and Td were each found to have a significant relationship with the development and deterioration of GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…Since plaque-induced gingival inflammation exacerbates the manifestations of PHT-induced GO [33], we exposed macrophage cultures to purified LPS from the periodontal pathogen, A. actinomycetemcomitans (Aa) and examined protein levels of MMPs, TIMPs and proinflammatory cytokines in conditioned media. Aa can be isolated from plaque samples of patients with GO [34] while Aa LPS, a TLR4 agonist, strongly induces MMP and pro-inflammatory cytokine expression [28-30,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Since plaque-induced gingival inflammation exacerbates the manifestations of PHT-induced GO [33], we exposed macrophage cultures to purified LPS from the periodontal pathogen, A. actinomycetemcomitans (Aa) and examined protein levels of MMPs, TIMPs and proinflammatory cytokines in conditioned media. Aa can be isolated from plaque samples of patients with GO [34] while Aa LPS, a TLR4 agonist, strongly induces MMP and pro-inflammatory cytokine expression [28-30,35]. …”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests a role of genetic predisposition, intracellular calcium metabolism exchange, molecular mechanisms [cytokines such as epidermal growth factor (EGF), platelet‐derived growth factor‐P], inactivation of collagenase and inflammation induced by bacterial plaque 5 . Also, Porphyromonas gingivalis type II fimA and Treponema denticola were each found to have a significant relationship with the development and deterioration of phenytoin‐influenced gingival overgrowth 17 . Other aetiological hypothesis includes immunoglobulin A deficiency in serum and saliva leading to local immune reactions 18 , decreased serum folate levels causing deterioration of the gingival sulcular epithelium 19 and low calcium ions in gingival fibroblasts 20 .…”
Section: Discussionmentioning
confidence: 99%
“…1a). There was lobulated gingival overgrowth in the edentulous ridge and around the teeth present [18,17,13,27 and 28] in the upper arch ( Fig. 1b).…”
Section: Case Reportmentioning
confidence: 99%
“…Takada et al [71] found that Prevotella intermedia (Pi) prevalence is higher in patients with PGO than in patients taking the medication but who did not develop that injury, and also those who did not use phenytoin. Akiyama et al [72] also examined subgingival bacterial profiles in subjects taking phenytoin who exhibited, or not, PGO. Quantitative analysis performed before and after periodontal treatment, revealed two bacterial species significantly associated with PGO, Treponema denticola (Td) and Porphyromonas gingivalis (Pg).…”
Section: Bacterial Biofilm and Pgo Developmentmentioning
confidence: 99%